The role of silver diamine fluoride as dental caries preventive and arresting agent: a systematic review and meta-analysis - Alqalaleef, Saeed S.; Alnakhli, Rabab A.; Ezzat, Yousef; AlQadi, Hamad I.; Aljilani, Abdulrahman D.; Natto, Zuhair S. (Frontiers in Oral Health, 2024)
BackgroundDental caries is a significant global health concern, impacting around 2.5 billion people worldwide. Conventional methods for managing dental caries have evolved to prioritize preventive measures and minimally invasive treatment alternatives. One of these approaches involves the application of silver diamine fluoride. Although effective, the limited use of SDF is attributed to concerns about potential long-term complications and other adverse effects.ObjectiveThis systematic review aims to assess the role of SDF in preventing and managing dental caries, evaluating its efficacy and adverse reactions.Material and methodsThis review adheres to PRISMA guidelines. An electronic search was performed on PubMed, Google Scholar, and CENTRAL to include peer-reviewed randomized controlled trials published between 2014 and 2024. The Cochrane risk of bias and GRADE tools were employed to evaluate the trials and ensure the certainty of the evidence. Statistical analysis was conducted to examine the effectiveness of SDF at the individual, tooth, and surface levels.ResultsFindings from 20 randomized controlled trials, which met the inclusion criteria, revealed that participants aged 1–50 showed promising results with follow-up intervals ranging from 1 to 30 months. The caries arrestment rate of silver diamine fluoride (SDF) varied from 25% to 99%.ConclusionThese results indicate that SDF could be an invaluable tool in combating dental caries, providing a less invasive and potentially more cost-effective alternative to traditional treatment methods. Nonetheless, further research is essential to comprehensively understand the potential of SDF in various settings and to optimize its application in clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO (CRD42024559853)